KEMANDIRIAN HAKIM DALAM PERSPEKTIF NEGARAWAN - Barhamudin, Barhamudin (Solusi, 2019)
The purpose of this study was to determine the independence of judges in accordance with Law Number 48 of 2009 in Statesperson's Perspectives. The research is a normative legal research that uses the law approach and the concept approach and data sources in this study are Primary Legal Materials; Secondary Legal Material and Tertiary Legal Material, the study found that all Judges must have the quality of statesmanship not just Constitutional judges, even those judges must behave and behave as statesmen, because judges are required to be impartial or independent in their duties to uphold truth based on law and justice. Judges must have the knowledge and expertise in administering the state, sufficient field of experience, and commitment to carry out and oversee the life of the state in accordance with the constitutional corridor. The judges are essentially statesmen, if seen from their duties and functions to uphold law and justice, not for the interests of others other than for the interests of the state, are not the elements of the state reflected in the interests of the people. Judges have the freedom to carry out their duties judicially and only answer to God.